2016
DOI: 10.1016/j.immuni.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A High-Dimensional Atlas of Human T Cell Diversity Reveals Tissue-Specific Trafficking and Cytokine Signatures

Abstract: Depending on the tissue microenvironment, T cells can differentiate into highly diverse subsets expressing unique trafficking receptors and cytokines. Studies of human lymphocytes have primarily focused on a limited number of parameters in blood, representing an incomplete view of the human immune system. Here, we have utilized mass cytometry to simultaneously analyze T cell trafficking and functional markers across eight different human tissues, including blood, lymphoid, and non-lymphoid tissues. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
256
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(281 citation statements)
references
References 48 publications
24
256
0
1
Order By: Relevance
“…Wong et al used mass cytometry to profile CD4+ T cells across eight human tissue types and described 75 different populations, including multiple T h 1 populations for each T H subset. Many cell populations were tissue-specific and differed based the expression of trafficking receptors and cytokine production [47••]. They observed that certain populations co-expressed “key” cytokines like IFN-γ, IL-4, and IL-17A that are typically restricted to a single CD4+ T H subset, in line with previous findings highlighting the phenotypic plasticity between CD4+ T H lineages [4851], reviewed in [52].…”
Section: High-dimensional Analyses Reveal An Expanded View Of Cd4+ T supporting
confidence: 65%
“…Wong et al used mass cytometry to profile CD4+ T cells across eight human tissue types and described 75 different populations, including multiple T h 1 populations for each T H subset. Many cell populations were tissue-specific and differed based the expression of trafficking receptors and cytokine production [47••]. They observed that certain populations co-expressed “key” cytokines like IFN-γ, IL-4, and IL-17A that are typically restricted to a single CD4+ T H subset, in line with previous findings highlighting the phenotypic plasticity between CD4+ T H lineages [4851], reviewed in [52].…”
Section: High-dimensional Analyses Reveal An Expanded View Of Cd4+ T supporting
confidence: 65%
“…As expected, CB Tconv control cells exhibited nearly complete methylation of the TSDR (3.8% ± 2.6% demethylated, n = 5; Figure 3B). CD8 + T cell contamination was minimal, particularly in cells expanded from CB (protocol 1: APB Tregs = 0.8% ± 0.4%, CB Tregs = 0.4% ± 0.3%, cryoCB Tregs = 0.5% ± 0.3%; Figure 3C), presumably from the lower frequency of CD8 + T cell in CB 37 . Again, these values were well below the clinical release criteria of ≤5% CD4 − CD8 + contamination.…”
Section: Resultsmentioning
confidence: 99%
“…CCR6 regulates cell migration into various anatomic sites including the intestinal mucosa [74-76]. CCR6 expression on CD4 + T-cells is associated with the Th17 lineage commitment [41, 70, 77].…”
Section: Discussionmentioning
confidence: 99%